New and old dual economy - Milenko Popović; Ivan Radević (Management : Journal of Contemporary Management Issues, 2022)
This paper aims to provide a possible explanation for the strange reoccurrence of the dual economy in developed countries. The dual economy is understood as consisting mainly of two sectors that differ in productivity, salaries, and related characteristics. It was hypothesized there is a relationship between secular stagnation, the slowdown in productivity growth, stagnation in wages, and the dual economy’s reoccurrence. In explaining this relationship, technological progress and the process of globalization, which have been prevalent in recent decades, play a crucial role. It is concluded that the era of the new dual economy and the productivity paradox represents a particular phase of economic growth. Since the phenomenon of the reoccurrence of the dual economy in developed countries has been noticed and studied only recently, further research is needed, focusing on the empirical studies.